ANALYSIS OF THE EFFECT OF RELATIONSHIP MARKETING AND PATIENTS’ SATISFACTION ON PATIENTS’ LOYALTY (A case in X Hospital) - Bernarto, Innoncentius; Satryautama, Jonathan (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2019)
Abstract: This study aims to examine whether there is a positive relationship between relationship marketing and patient’s satisfaction on patients’ loyalty. There were 100 inpatients of VIP class and class 1 of X Hospital involved as the respondents chosen through a convenience sampling method. The instrument used to collect the data was a questionnaire which was also tested for its validity and reliability and analysed using PLS-SEM of Smart PLS 3.0 program. The results revealed that relationship marketing has a positive effect on loyalty and satisfaction and satisfaction has a positive effect on loyalty.Keywords : Relationship Marketing,Satisfaction, Loyalty, Hospitals